The Effect of Using Summarizing Technique on Students' Reading Comprehension of Recount Text (A Study at the Tenth Grade Students of SMA Negeri 5 Padangsidimpuan) - NURLIANA HUTAPEA (JURNAL LINER (Language Intelligence and Educational Research), 2018)
The aim of this research is to know: 1) the application of using summarizing technique, 2) the students’ reading comprehension of recount text before and after using summarizing technique, 3) whether there is a significant effect of using summarizing technique on students’ reading comprehension of recount text at the tenth grade students of SMA Negeri 5 Padangsidimpuan. This study is carried on by using experimental method. The population of this research is all the tenth grade which are divided into seven classes and total are 248 students. The sample consists of 35 students by using systematic sampling. The data is collected by giving observation and test. After collecting the data, the mean of the application description of using summarizing techniqueis 3.50. It is categorized “Very Good”. The mean of students’ reading comprehension of recount text before using summarizing techniqueis 71.14. It is categorized “Good”. The students’ reading comprehension of recount text after using summarizing techniqueis 84.71. It is categorized “Very Good”. The result of ttestis 8.15, and ttable 5% significant level is 2.03. It means that there is a significant effect of usingsummarizing techniqueon students’ reading comprehension of recount text at the tenth grade students of SMA Negeri 5 Padangsidimpuan. Keywords: Summarizing, Reading Comprehension, Recount Text.